17β‐Oestradiol enhances the expansion and activation of myeloid‐derived suppressor cells via signal transducer and activator of transcription (STAT)−3 signalling in human pregnancy. (13th April 2016) - Pan, T.; Zhong, L.; Wu, S.; Cao, Y.; Yang, Q.; Cai, Z.; Cai, X.; Zhao, W.; Ma, N.; Zhang, W.; Zhang, H.; Zhou, J.
Summary: During a successful pregnancy, the maternal immune system plays a critical role in maintaining immunotolerance towards semi‐allogeneic fetal antigens. Recent studies have indicated that myeloid‐derived suppressor cells (MDSCs) are active players in establishing fetal–maternal tolerance; however, the underlying mechanism remains poorly understood. In this study, we observed a significant expansion of monocytic MDSCs (M‐MDSCs) in the peripheral blood of pregnant women, which suppressed T cell responses in a reactive oxygen species‐dependent manner and required cell–cell contact. The number of M‐MDSCs correlated positively with serum oestrogen and progesterone levels. Administration of 17β‐oestradiol, but not progesterone, enhanced both the expansion and suppressive activity of M‐MDSCs through signal transducer and activator of transcription (STAT)‐3. Pretreatment with STAT‐3 inhibitor JSI‐124 almost completely abrogated the effects of 17β‐oestradiol on MDSCs. Collectively, these results demonstrate that 17β‐oestradiol‐induced STAT‐3 signalling plays an important role in both the expansion and activation of MDSCs during human pregnancy, which may benefit the development of novel therapeutic strategies for prevention of immune‐related miscarriage.